Ekonomista z Podola. Jerzy Zdziechowski – życiorys, poglądy oraz działalność publiczna - Klimiuk, Zbigniew (Przegląd Wschodnioeuropejski, 2023)
Zdziechowski Jerzy (1880–1975) was a politician, economist and economic activist. In the years 1917–1918 he was a member of the Polish Council of the Inter-Party Union in Russia and a co-organizer of the Polish Corps in Russia. In 1919, he was one of the main participants in the failed coup d’etat attempting to overthrow the government of Jędrzej Moraczewski. In the years 1922–1927, he was a member of the Sejm from the Popular National Union. In the years 1925–1926, he was the Minister of the Treasury in the government of A. Skrzyński. He developed the economic and financial program for stabilizing the Polish zloty, which caused such side effects as, i.a.: reduced employment, lowered wages, and reduced exports of agricultural products, as well as significant increases in taxes and prices. However, the program allowed for achieving a balanced budget. The program’s implementation resulted in the withdrawal of the Polish Socialist Party from the ruling coalition and led to the fall of the government. In the years 1926–1933, he was a member of the Council of the Camp of Great Poland, which was founded and led by Roman Dmowski. Until 1939, he was an activist of economic organizations. From September 1939, Jerzy Zdziechowski resided abroad. After World War II, he was the chairman of the Executive Department of the Political Council in London on behalf of the National Party. Jerzy Zdziechowski was characterized by theoretical eradication and the ability to achieve macroeconomic goals within the framework of economic policy, which he proved by managing financial matters in the years 1925-26 as well as by his creative criticism of the politics in 1926-39.